A history of demoniac possessions in Loudun. An analysis of Michel de Certeau's work on a political-religious fact - Rodrigues da Costa, Otavio Barduzzi [UNESP] (Pontificia Univ Catolica Sao Paulo, Fac Teologia, 2017)
The phenomenon of belief in demonic possessions always appears in times of crisis. The intention of this communication is to report the vision of Michel de Certeau, among others, on a fact of possession that occurred in Loudun and shows that religious motives, for some time in history, have been and are still being used for political manipulation. With great documentary and literary analysis, allied to intense research on the city's folklore and imagery, Certeau shows a perspective on the history of religions in the least different. In the construction of his reasoning and his research, contradictory histories emerge, each at different times and places and each one connected in political and epistemological transformations, of Certeau not only maintains an unconventional authorial posture, but more importantly: it shows the reader That which is lost, missing and fragmented in the process of writing official history.
Keywords: Demonic possessions; Religion History; Loudun